2022
DOI: 10.1186/s12913-021-07448-3
|View full text |Cite
|
Sign up to set email alerts
|

Improving hospital-based processes for effective implementation of Government funded health insurance schemes: evidence from early implementation of PM-JAY in India

Abstract: Background Government-sponsored health insurance schemes (GSHIS) aim to improve access to and utilization of healthcare services and offer financial protection to the population. India’s Ayushman Bharat Pradhan Mantri Jan Arogya Yojana (PM-JAY) is one such GSHIS. This paper aims to understand how the processes put in place to manage hospital-based transactions, from the time a beneficiary arrives at the hospital to discharge are being implemented in PM-JAY and how to improve them to strengthen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…Time taken for ‘pre-authorization approval’ can be high if (a) at hospital level AM is submitting incomplete ‘admission and pre-authorization request’ resulting in repeated queries from the insurer, (b) the insurer lacks the capacity to process the received ‘admission and pre-authorization request’ on time. It has been suggested that the time required for completing hospital-based processes that involve AMs can be reduced by investing in capacity-building efforts for AMs [ 15 ]. The results of the present study highlight a need to focus on capacity-building initiatives for AMs in Madhya Pradesh as compared to Gujarat, and within Madhya Pradesh to prioritize such initiatives for AMs working in private hospitals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Time taken for ‘pre-authorization approval’ can be high if (a) at hospital level AM is submitting incomplete ‘admission and pre-authorization request’ resulting in repeated queries from the insurer, (b) the insurer lacks the capacity to process the received ‘admission and pre-authorization request’ on time. It has been suggested that the time required for completing hospital-based processes that involve AMs can be reduced by investing in capacity-building efforts for AMs [ 15 ]. The results of the present study highlight a need to focus on capacity-building initiatives for AMs in Madhya Pradesh as compared to Gujarat, and within Madhya Pradesh to prioritize such initiatives for AMs working in private hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…This was found to be more relevant for patients with conditions, like cancer, that require treatment by a team of doctors using multiple treatment modalities. It has also been reported that the patients are asked to pay for the difference of costs between the treatment preferred by the healthcare providers (for example, medicine or an implant for treatment of a cardiovascular condition) and that covered under the scheme [ 15 ]. Irrespective of the reasons, OOP payments affect the financial and physical coverage of the GSHIS scheme and negatively affect user satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the last 10 years, EIR has been used successfully to improve the use of knowledge in decision making at different levels within health systems, resulting in tangible outcomes that have been documented in numerous publications. [8][9][10][11][12] The EIR approach, as demonstrated by the AHI, has shown its potential for strengthening the learning capacity of health systems and improving health systems' performance. While further evaluations of the EIR approach are needed, there is clearly strong support for this approach to contribute significantly to improving policy and program implementation.…”
Section: Discussionmentioning
confidence: 99%
“…In these instances, workshops focused on the interpretation and dissemination of the research findings, which have been critical in helping to adapt and improve program delivery. [9][10][11] In Argentina, EIR resulted in the development of new monitoring indicators to improve the implementation of the perinatal health policy. In Chile, research findings led to the establishment of a training program on reproductive rights that targeted municipal health facilities.…”
Section: History and Evolution Of Eirmentioning
confidence: 99%